Loss of Caveolin-1 Impairs Light Flicker-Induced Neurovascular Coupling at the Optic Nerve Head - Loo, Jing Hong; Lee, Ying Shi; Woon, Chang Yi; Yong, Victor H. K.; Tan, Bingyao; Schmetterer, Leopold; Chong, Rachel S. (Frontiers in Neuroscience, 2021)
Glaucoma is a neurodegenerative disease, which results in characteristic visual field defects. Intraocular pressure (IOP) remains the main risk factor for this leading cause of blindness. Recent studies suggest that disturbances in neurovascular coupling (NVC) may be associated with glaucoma. The resultant imbalance between vascular perfusion and neuronal stimulation in the eye may precede retinal ganglion cell (RGC) loss and increase the susceptibility of the eye to raised IOP and glaucomatous degeneration. Caveolin-1 (Cav-1) is an integral scaffolding membrane protein found abundantly in retinal glial and vascular tissues, with possible involvement in regulating the neurovascular coupling response. Mutations in Cav-1 have been identified as a major genetic risk factor for glaucoma. Therefore, we aim to evaluate the effects of Cav-1 depletion on neurovascular coupling, retinal vessel characteristics, RGC density and the positive scotopic threshold response (pSTR) in Cav-1 knockout (KO) versus wild type C57/Bl6 mice (WT). Following light flicker stimulation of the retina, Cav-1 KO mice showed a smaller increase in perfusion at the optic nerve head and peripapillary arteries, suggesting defective neurovascular coupling. Evaluation of the superficial capillary plexus in Cav-1 KO mice also revealed significant differences in vascular morphology with higher vessel density, junction density and decreased average vessel length. Cav-1 KO mice exhibited higher IOP and lower pSTR amplitude. However, there was no significant difference in RGC density between Cav-1 KO and wild type mice. These findings highlight the role of Cav-1 in regulating neurovascular coupling and IOP and suggest that the loss of Cav-1 may predispose to vascular dysfunction and decreased RGC signaling in the absence of structural loss. Current treatment for glaucoma relies heavily on IOP-lowering drugs, however there is an immense potential for new therapeutic strategies that increase Cav-1 expression or augment its downstream signaling in order to avert vascular dysfunction and glaucomatous change.